A 60% crisis: Mortality and hypertension-driven intracranial haemorrhage at a South African tertiary hospital - Umar Jacobs; Thaakir-Ahmed Jacobs; Janneke Pienaar; Sideeqa Jakoet; Aaqilah Fataar; Neshaad Schrueder; Sa'ad Lahri (Journal of the Colleges of Medicine of South Africa)
Background: Spontaneous intracranial haemorrhage (ICH) is a significant cause of morbidity and mortality worldwide, with a disproportionate burden in low- and middle-income countries. Data on ICH in South Africa are limited, hindering targeted intervention efforts.